Residence as a Factor of Social Stratification - Vakhshtayn*Viktor (Journal of Economic Sociology, 2010)
The goal of the research is to study the impact of resident differences on the stratification in societies of micro, mezzo and macro levels: starting from small social group till society. The author shows that inequality in terms of lifelong as a factor of social stratification independent from the level (small group, organization, city, and society) has a row of specific characteristics. The residence appearance always means the existence of some relations space (territory) and migration processes. In different societies resident stratification system has the same formation stages. Residence is based on “resources” and “values” as well as on formal and informal institutions that support the existed resident inequality. So the author concludes that this entire let us speak about reasonable analysis of residence as rather stable factor of stratification and its impact on the society structure.